Financing of Innovative Activity and Investment Management: Institutional and Fiscal Approaches - Gafurova Umida Fatikhovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
In the contemporary global economy, the intensification of market competition and the growing scarcity of resources have fundamentally transformed the determinants of sustainable economic performance. Under these conditions, the decisive factor in enhancing production efficiency, advancing industries to higher technological stages, and strengthening the strategic positions of economic agents lies in the systemic integration of innovation activity with investment processes. Investment in modern economic systems is no longer confined to the accumulation of tangible assets; rather, it represents a multidimensional economic category encompassing scientific and technological capacity, human capital development, and the generation and diffusion of intellectual value.